2000
DOI: 10.1055/s-2000-15289
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin Injection as an Adjunct when Planning Hand Surgery in Children with Spastic Hemiplegia

Abstract: The usefulness of botulinum toxin A treatment when planning hand surgery in eight children with spastic hemiplegia was evaluated. The hand function of the children was assessed before and after treatment using a test battery consisting of quantitative and qualitative functional assessment. The results of preoperative botulinum treatment supported surgical intervention in four children and serial botulinum treatment in three children. In one child, the preoperative botulinum treatment provided no additional inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…In view of the small sample size, results were analysed individually and are summarized in Figures 1(a-f ) and 2(a-e) and Tables IV-VI. The parents recognized the tone reduction onset within a mean of 4.2 days (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and the decline after a mean of 3.4 months (range 1.5-5). All patients, parents and therapists reported relaxation, better posture and smoother movement patterns in the treated arm, this also being seen as change in MAS, ULPRS, caregiver satisfaction and cosmetic appearance scores.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the small sample size, results were analysed individually and are summarized in Figures 1(a-f ) and 2(a-e) and Tables IV-VI. The parents recognized the tone reduction onset within a mean of 4.2 days (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and the decline after a mean of 3.4 months (range 1.5-5). All patients, parents and therapists reported relaxation, better posture and smoother movement patterns in the treated arm, this also being seen as change in MAS, ULPRS, caregiver satisfaction and cosmetic appearance scores.…”
Section: Resultsmentioning
confidence: 99%
“…The few studies investigating its clinical effectiveness on the spastic upper limb have shown a reduction in spasticity, increase in range of movement and improvement in function, cosmetic appearance and flexibility of movement pattern [7][8][9][10][11][12][13]. Outcome measurements have usually focused on impairment and grip function and, except for the latest studies, to a lesser extent on bimanual functions, self-care and daily activities.…”
Section: Introductionmentioning
confidence: 99%
“…The high dose was in the range of BTX-A that is in current clinical usage and in published articles. 3,5,[7][8][9] The low-dose group received 50% of the dosage of the high-dose group for each muscle group injected. We hypothesized that a low dose would be more effective because it would permit a reduction in tone and subsequent improvement in function without causing significant weakness.…”
mentioning
confidence: 99%
“…However, there was no significant improvement of fine motor function for the entire group. Only a few open labelled trials are available [70][71][72]. The main clinical indication is for functional or cosmetic purposes, e.g.…”
Section: Review Of Botulinum Toxin In Treating Spasticity Of Upper LImentioning
confidence: 99%
“…This review attempts to analyse the current level of evidence in the use of Botox in treating lower limb or upper limb spasticity [67][68][69][70][71][72][73] and drooling [74][75][76][77]. Summary tables of most available Randomized Controlled Trials (RCT) and open labelled (OL) trials up to April 2003 are presented in tables 3-7.…”
Section: Introductionmentioning
confidence: 99%